A hierarchy of predictors for dementia‐free survival in old‐age: results of the AgeCoDe study. (22nd March 2013) - Luck, T.; Riedel‐Heller, S. G.; Luppa, M.; Wiese, B.; Bachmann, C.; Jessen, F.; Bickel, H.; Weyerer, S.; Pentzek, M.; König, H.‐H.; Prokein, J.; Eisele, M.; et al.
<x xml:space="preserve">Abstract</x> Objective Progression from cognitive impairment (CI) to dementia is predicted by several factors, but their relative importance and interaction are unclear. Method We investigated numerous such factors in the AgeCoDe study, a longitudinal study of general practice patients aged 75+. We used recursive partitioning analysis (RPA) to identify hierarchical patterns of baseline covariates that predicted dementia‐free survival. Results Among 784 non‐demented patients with CI, 157 (20.0%) developed dementia over a follow‐up interval of 4.5 years. RPA showed that more severe cognitive compromise, revealed by a Mini‐Mental State Examination (MMSE) score < 27.47, was the strongest predictor of imminent dementia. Dementia‐free survival time was shortest (mean 2.4 years) in such low‐scoring patients who also had impaired instrumental activities of daily living (iADL) and subjective memory impairment with related worry (SMI‐w). Patients with identical characteristics but without SMI‐w had an estimated mean dementia‐free survival time of 3.8 years, which was still shorter than in patients who had subthreshold MMSE scores but intact iADL (4.2–5.2 years). Conclusion Hierarchical patterns of readily available covariates can predict dementia‐free survival in older general practice patients with CI. Although less widely appreciated than other variables, iADL impairment appears to be an especially noteworthy predictor of progression to dementia.